Analisis Kualitas Butir Soal UTS Mata Pelajaran IPA Tahun Pelajaran 2019/2020 Kelas VII di SMPN 6 Kota Langsa - Cindy Rasta Br Ginting; Dion Bagus Ds; Nurul Yusya Miranti; Nurmasyitah Nurmasyitah (Jurnal Pendidikan Fisika dan Sains, 2020)
The purpose of this study is to determine the quality of the results of the vii class science class in 2019/2020, a class of validity, reliability, depth of adversity and contrasting power. And this study USES a descriptive method. The subject in this study is a student class vii middle school n 6 langsa. Data-collection techniques are done using methods of documentation and observation. Data obtained use manual calculations by helping excel programs. This study is: (1) based on validity, problem no. 1 is low-predicated, validity of article 2 is insufficient, validity of article 3 is extremely low, and the validity of grains of 4-5 is fairly categorized. (2) reliably, the results of these studies have found that the peculiar midterm problems for the class vii class 6 of langsa for the 2019/2020 school are not religious, (3) based on reclassification power, from exam problems are low, only article no. 4 has enough categories. (4) for her level of suffering from no. 1 to no. 5, she was categorized as a simple group. Tests are good as a gauge when they meet the following requirement: good validity, good reliability, good objectivity, normal practicality and good economic value. Well, according to research conducted, the fact that entire grains of matter were rated as inferior. Because of validity, reliability, contrition power and severity it does not meet well-defined standard scores.